2022
DOI: 10.1128/spectrum.01127-22
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Colistin Resistance Gene mcr-10.1 Carried by Inc pA1763-KPC Plasmid pSL12517-mcr10.1 in Enterobacter cloacae in Sierra Leone

Abstract: Colistin is used as one of the last available choices of antibiotics for patients infected by carbapenem-resistant bacterial strains, but the unrestricted use of colistin aggravated the acquisition and dissemination of mobile colistin resistance ( mcr ) genes. So far, 10 mcr genes have been reported in four continents around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
9
2
Order By: Relevance
“…For instance, Wang et al [ 8 ] obtained a colistin-resistant E. roggenkampi strain when transferring mcr-10 from a susceptible strain by cloning. Expression data by Guan et al [ 18 ] and Xu et al [ 21 ] further suggest that other, chromosomic genes might mediate the high level of colistin resistance observed in their Enterobacter spp. isolates.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, Wang et al [ 8 ] obtained a colistin-resistant E. roggenkampi strain when transferring mcr-10 from a susceptible strain by cloning. Expression data by Guan et al [ 18 ] and Xu et al [ 21 ] further suggest that other, chromosomic genes might mediate the high level of colistin resistance observed in their Enterobacter spp. isolates.…”
Section: Discussionmentioning
confidence: 98%
“…This specific colistin resistance gene has been so far isolated mostly in Enterobacter spp. [ 8 , 17 , 18 ], but was described also in Klebsiella spp. [ 14 , 19 ] and in E. coli [ 20 ], showing, like other mcr genes, the potential for a wide host range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli [ 49 ], S. enterica [ 13 ], ECC [ 17 ], and K. pneumoniae [ 50 ]. In contrast, mcr-10 was almost hosted in ECC and sporadically isolated from environment [ 16 ], animal [ 51 ] and clinical samples [ 52 ]. Previous studies have shown that mcr-9 and mcr-10 were frequently carried in ECC by using single centre or endemic data [ 14 , 16 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten mcr homologues ( mcr -1–10) have so far been identified, and mcr-1 continues to be the main character and is widely distributed [ 10 , 11 , 12 ]. The MIC of colistin in E. coli have been shown to increase by 4 to 8-fold when the mcr-1 gene is present, indicating that mcr-1 alone can provide adequate resistance against colistin in E. coli and other Enterobacteriaceae [ 2 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%